1980
DOI: 10.1113/jphysiol.1980.sp013467
|View full text |Cite
|
Sign up to set email alerts
|

The uptake and release of [3H]glycine in the goldfish retina.

Abstract: 2. The high-affinity mechanism, and probably also the low-affinity mechanism, is temperature-and Na+-dependent.3. The low-affinity mechanism for glycine uptake is not affected by 5 mM-isoleucine, methionine and valine in the medium. However, it is inhibited more than 90 % by 5 mM-alanine, proline and serine in the medium. This result indicates that the low-affinity transport for glycine may go through system A of the neutral amino acid transport system which is present in most tissues to transport glycine and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
15
0

Year Published

1980
1980
2002
2002

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 49 publications
(16 citation statements)
references
References 30 publications
1
15
0
Order By: Relevance
“…Neurons using other amino acids such as GABA or glycine as neurotransmitters usually possess a high-affinity system for the uptake of the transmitter but not for the uptake of its precursor (7,9,10,(27)(28)(29)(30)(31). In this regard, it is of interest to compare our findings on mammalian cones with those for a known GABA neuron, the type H1 horizontal cell of the goldfish retina.…”
Section: Resultsmentioning
confidence: 99%
“…Neurons using other amino acids such as GABA or glycine as neurotransmitters usually possess a high-affinity system for the uptake of the transmitter but not for the uptake of its precursor (7,9,10,(27)(28)(29)(30)(31). In this regard, it is of interest to compare our findings on mammalian cones with those for a known GABA neuron, the type H1 horizontal cell of the goldfish retina.…”
Section: Resultsmentioning
confidence: 99%
“…The incubation experiments indicate that the uptake is not mediated by a transporter for choline, sarcosine or the intermediary metabolites, and the high-affinity glycine transporters GLYT1 and GLYT2 have already been excluded. The glycine does not appear to be taken up by ubiquitous low-affinity glycine transporters, which should be blocked by excess alanine, proline or serine (Chin and Lam, 1980). It might appear that rabbit cholinergic amacrine cells express a low-affinity glycine transporter that is not found in other types of retinal neurons or in the cholinergic amacrine cells of other vertebrates.…”
Section: Glycine Accumulation By Cholinergic Amacrine Cellsmentioning
confidence: 92%
“…3 H-glycine-uptake experiments on the retina indicated that 90% of the low-affinity uptake can be inhibited by 5 mM alanine, proline or serine (Chin and Lam, 1980;Kong et al, 1980;Marc, 1984). However, none of these amino acids had any significant effect on the sarcosine-induced accumulation of glycine by the cholinergic cells (Fig.…”
Section: Mechanism Of Sarcosine-induced Glycine Accumulationmentioning
confidence: 96%
“…The isolated cell preparation allowed us to characterize the response of the cells to putative retinal neurotransmitters without the complications of interpretation arising from the wealth of synaptic connexions, and the existence of neurotransmitter uptake mechanisms in the intact retina. The neurotransmitters tested were glutamate, aspartate, cadaverine, putrescine and N-acetylhistidine, which are known to be released from photoreceptors on depolarization and have been suggested as candidates for the photoreceptor transmitter (Cervetto & MacNichol, 1972; Murakami,126 BIPOLAR CELL SYNAPTIC CURRENTS Ohtsu & Ohtsuka, 1972;Shiells, Falk & Naghshineh, 1981;, 1983a, 1985Miller & Schwartz, 1983), and y-aminobutyric acid (GABA) and glycine, which are thought to mediate inhibitory input to bipolar cells from horizontal, amacrine and interplexiform cells (Hollyfield, Rayborn, Sarthy & Lam, 1979;Chiu & Lam, 1980;Rayborn, Sarthy, Lam & Hollyfield, 1981;Miller, Frumkes, Slaughter & Dacheux, 1981;Wu, 1986). Use of the retinal slice preparation allowed a comparison of the properties of isolated cells with those of cells in the retina.…”
Section: Introductionmentioning
confidence: 99%